2006
DOI: 10.1111/j.1463-5224.2007.00481.x
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal development of canine axial globe length measured by B‐scan ultrasonography

Abstract: A reverse transformation of the formula can be used to predict AGL in mesocephalic cross-bred dogs: AGL = 10.847 * age in weeks 0.1653.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
29
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 9 publications
(6 reference statements)
7
29
0
6
Order By: Relevance
“…This finding was also reported by Tuntivanich et al (2007). Boroffka (2005) assessed the intraeye structure development in four fetuses in prenatal care and in 11 puppies in postnatal care using B-scan ultrasonography and observed that both in the pre-and post natal care there was continuous growth of the eye depth, anterior chamber, lens and vitreous chamber.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…This finding was also reported by Tuntivanich et al (2007). Boroffka (2005) assessed the intraeye structure development in four fetuses in prenatal care and in 11 puppies in postnatal care using B-scan ultrasonography and observed that both in the pre-and post natal care there was continuous growth of the eye depth, anterior chamber, lens and vitreous chamber.…”
Section: Discussionsupporting
confidence: 59%
“…According to the statistical analysis, there was no evidence of difference (p>0.05) in the measurements of the eyeball segments between the right and left eyes (Table 1), that presented great homogeneity, as reported by Schiffer et al (1982), Gaiddon et al (1991), Williams (2004), Boroffka et al (2006), Tuntivanich et al (2007) and Beserra et al (2009).…”
Section: Discussionmentioning
confidence: 53%
“…No differences were observed between mean values found for intraocular structures when comparing between right and left eyes of animals from the same conformational group, which is in agreement with data reported by other authors (Williams, 2004;Tuntivanich et al, 2007). With this, it is possible to say that measurements of the normal eye can provide reliable parameters for determination of the size of eye prosthesis in cases of malformation or enucleation of the opposite eye.…”
Section: Resultssupporting
confidence: 81%
“…De acordo com o relatado por outros autores (Gilger et al 1998, Gonçalves et al 2000, Tuntivanich et al 2007, Beserra et al 2009, Gonçalves et al 2009) a comparação entre os olhos direito e esquerdo, em ambos os grupos deste estudo, não diferiram à estatística. Porém, contrariando o relatado por estes autores, foi observada diferença significativa em D4 de machos e fêmeas no grupo GB, apresentando as fêmeas, medida superior a dos machos.…”
Section: Discussionunclassified